In search for the criteria of absolute pitch - RAKOWSKI, Andrzej; MORAWSKA-BÜNGELER, Marietta (Archives of Acoustics, 1987)
A series of experiments has been performed in order to find specific features of pitch memory in persons possessing the so-called absolute pitch.Sixty one music students were given a test of passive absolute pitch (pitch-naming test); then a part of this group was subjected to another test in order to determine their ability to produce required musical pitch without being given any reference tone (active absolute pitch). A criterion for absolute pitch was proposed on the basis of the evaluation of the precision of tuning a pure-tone generator to the required musical pitch. Finally, two musicians, one of them possessing absolute-pitch, were given a task of tuning a pure-tone generator to the pitch of a standard after various delay times. The results were presented in the form of pitch-forgetting curves.